STAY OF EXECUTION OF SENTENCE - THEORETICAL AND PRACTICAL APPROACH - Alina-Marilena ŢUCĂ (Challenges of the Knowledge Society, 2021)
The completion of the activity of achieving the criminal justice goals involves immediate execution of final criminal judgments and continuity in the enforcement activity. However, there are also exceptional situations, where criminal enforcement is suspended as a result of the intervention of some impediments in the execution of the sentence. The stay of execution of prison or life imprisonment sentence is precisely such a situation, as regulated by Section II, Chapter III “Other provisions regarding execution”, Title V “Execution of criminal judgments” of the Code of Criminal Procedure. The stay of execution of sentence is not a removal of the penalty applied to the convict, but merely a postponement of the moment from which it should begin, making up an exception to the rule of immediate execution of the criminal judgment. In order to avoid situations of unjustified stay of execution of sentence or even removal of execution of sentence, the legislator expressly and restrictively laid down the instances and conditions in which the convicted person may obtain the stay of execution of sentence. Without claiming to be exhaustive, this study may serve as a basis for certain legal or practical clarifications in connection with the institution of stay of execution of prison or life imprisonment sentence.